2003
DOI: 10.1093/emboj/cdg079
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ORC-binding sites are required for efficient MCM loading and origin firing in fission yeast

Abstract: In most eukaryotes, replication origins are composed of long chromosome regions, and the exact sequences required for origin recognition complex (ORC) and minichromosome maintenance (MCM) complex association remain elusive. Here, we show that two stretches of adenine/thymine residues are collectively essential for a fission yeast chromosomal origin. Chromatin immunoprecipitation assays revealed that the ORC subunits are located within a 1 kb region of ori2004. Analyses of deletion derivatives of ori2004 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
58
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 45 publications
6
58
0
3
Order By: Relevance
“…Thus, the overall affinity of SpOrc4 for such a sequence would be a complex function of the number of possible binding modes and the binding affinity of each mode and would be expected to increase with AT content and length. Consistent with these ideas, it has been demonstrated experimentally that SpOrc4 has significant affinity for multiple sites within a single ars element (41)(42)(43)46). Moreover, genetic studies have shown that sequences capable of functioning as origins contain multiple redundant AT-rich elements that contribute to activity (14-16, 18, 38).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the overall affinity of SpOrc4 for such a sequence would be a complex function of the number of possible binding modes and the binding affinity of each mode and would be expected to increase with AT content and length. Consistent with these ideas, it has been demonstrated experimentally that SpOrc4 has significant affinity for multiple sites within a single ars element (41)(42)(43)46). Moreover, genetic studies have shown that sequences capable of functioning as origins contain multiple redundant AT-rich elements that contribute to activity (14-16, 18, 38).…”
Section: Discussionmentioning
confidence: 88%
“…ars2004, located in the left arm of chromosome II (Fig. 1A), is a well-characterized early origin (Okuno et al 1999;Takahashi et al 2003) where initiation factors assemble efficiently at the onset of S phase (Yamada et al 2004;Yabuuchi et al 2006). AT2088/ARS745 (Maundrell et al 1988;Segurado et al 2003) is a late/dormant origin located in the right arm of chromosome II (Fig.…”
Section: Identification Of the Dna Element That Controls Replication mentioning
confidence: 99%
“…We used primers previously designed by Ogawa et al, 1999 to amplify sequences specific to origin DNA (ars2004 or ars3002) and to nonARS DNA, located ϳ25 kb centromere-proximal to ars2004 on chromosome II (Ogawa et al, 1999). Similar primers have been successfully used for the analysis of Orc1 and Mcm binding to origin DNA (Ogawa et al, 1999;Takahashi and Masukata, 2001;Takahashi et al, 2003). These primer sets were used in quantitative PCR on DNA prepared either from immunoprecipitated chromatin fractions or from total DNA isolated from whole cell soluble extracts.…”
mentioning
confidence: 99%